Experiment and Quantification of Weight: Late-Renaissance and Early Modern Medical, Mineralogical and Chemical Discussions on the Weights of Metals - Manzo, Silvia (2020)
This paper explores how a set of observations on the weight of lead were interpreted and assessed between the 1540s and the 1630s across three different interconnecting disciplines: medicine, mineralogy and chemistry. The epistemic import of these discussions will be demonstrated by showing: 1) the changing role and articulation of experience and quantification in the investigation of metals; and 2) the notions associated with weight in different disciplinary frameworks. In medicine and mineralogy, weight was not considered as a specific subject of inquiry in itself, but as a "sign" indicating other relevant properties of metals. In contrast, the chemistry tradition was increasingly concerned with the specific investigation of weight as a property of matter, as seen in the debates that took place in the "chemical revolution." In addition, this study will reveal the versatility, polysemy, and parallel purposes of the recourse to experiential knowledge in different contexts, where the same "facts" operate within different disciplines.
Keywords: Weight; Lead; Quantification; Experiments; Calcination of metals; Conservation of mass; Galen; Georg Agricola; Vannoccio Biringuccio; Julius Caesar Scaliger; Girolamo Cardano; Gabriele Falloppio; Andrea Cesalpino; Girolamo Mercuriale; Peter Monau, Giovanni Battista Cortesi; Johann Gerhard; Jean Rey